2021
DOI: 10.1097/inf.0000000000003227
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Histopathology of Coronavirus Disease 2019-Related Deaths in African Children

Abstract: Background: Globally, very few childhood deaths have been attributed to coronavirus disease 2019 . We evaluated clinical, microbiologic and postmortem histopathologic findings in childhood deaths in whom severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified antemortem or postmortem. Methods: Surveillance of childhood deaths was ongoing during the initial COVID-19 outbreak in South Africa from April 14, 2020, to August 31, 2020. All children hospitalized during this time had a SARS-CoV-2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The greater frequency of fibrin platelet thrombi in the COVID+ decedents when compared to COVID- decedents suggests that this is one of the manifestations of this infection and that it is systemic in nature, being found in the pulmonary vasculature, portal vein, hepatic vein and hepatic arterioles. Similar systemic fibrin platelet thrombi have also been found in other series of both adult and paediatric decedents [ 34 , 35 ]. On the other hand, the Polak et al classification, by not including the exudative phase, misses those COVID+ deaths in the early phase of illness that have only intra-alveolar exudation of fluid, protein and hyaline membrane formation.…”
Section: Discussionsupporting
confidence: 83%
“…The greater frequency of fibrin platelet thrombi in the COVID+ decedents when compared to COVID- decedents suggests that this is one of the manifestations of this infection and that it is systemic in nature, being found in the pulmonary vasculature, portal vein, hepatic vein and hepatic arterioles. Similar systemic fibrin platelet thrombi have also been found in other series of both adult and paediatric decedents [ 34 , 35 ]. On the other hand, the Polak et al classification, by not including the exudative phase, misses those COVID+ deaths in the early phase of illness that have only intra-alveolar exudation of fluid, protein and hyaline membrane formation.…”
Section: Discussionsupporting
confidence: 83%
“…This review was undertaken before COVID-19 pneumonia data in children was reported. However, subsequently, a South African study conducted during the peak of the first wave of the COVID-19 outbreak identified histopathology lung findings in 11 cases in which COVID-19 was considered to have contributed to the child’s death [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem histopathological findings (13 days after the SARS-CoV-2 positive result), obtained by targeted minimal invasive tissue sampling, revealed hyaline membrane, type II pneumocyte proliferation, interstitial inflammation, markedly reactive bronchial cells, and intravascular thrombi, which could be consistent with COVID-19. The immediate cause of death was assigned to be attributed to A. baumannii nosocomial sepsis with the antecedent cause related to nosocomial SARS-CoV-2 and acute respiratory distress syndrome due to SARS-CoV-2 ( 32 ).…”
Section: Resultsmentioning
confidence: 99%